Excellent Charge Transfer over Highly Stable LaCoO3 Perovskites for CO2 Photoreduction to Solar Fuels under Visible Light - Mohamed Madi; Muhammad Tahir; Zaki Yamani Zakaria; Hajar Alias (Chemical Engineering Transactions, 2022)
Global warming due to the combustion of fossil fuels has a major concern today. Therefore, the photocatalytic CO2 reduction of valuable chemicals and fuels has become a hotly debated topic of study. This is due to the fact that this can simultaneously resolve the energy crisis and environmental issues. In this regard, a lot of research has gone into developing efficient photocatalysts for CO2 reduction. Lanthanum cobalt perovskite (LaCoO3) is one the semiconductors with catalytic capabilities, excellent stability, nontoxic, and low costs. The properties of LaCoO3 perovskite based on the use of transition metals such as lanthanum (La) and cobalt (Co) make it applicable for photocatalytic enhancement of photoactivity. This is due to its visible light activity, ability to trap electrons, rapid charge carrier mobility, and conductivity. LaCoO3 nanoparticles are synthesized through the hydrothermal technique. This study reveals that LaCoO3 nanoparticles synthesized by hydrothermal method have a larger surface area and narrow bandgaps, resulting in a greater adsorptive capacity, increased visible light excitation, and an increase in the number of active sites for photocatalytic CO2 reduction. The XRD, FTIR, and SEM was used to analyses the LaCoO3 nanocatalysts. After 4 h with a 0.05 g catalyst loading and (CO2 + water) as a reducing agent at normal temperature and pressure, the use of LaCoO3 resulted in CO and CH4 production rates of 110.4, and 28.5 mol g-1. The high selectivity toward CO was certainly related to a greater surface area with enhanced light absorption. The LaCoO3 photocatalyst was also investigated under a number of operating conditions, including photocatalyst loading, and reducing agents. Using three different catalyst loadings of 0.025, 0.05, and 0.1 g, the optimal catalyst loading was 0.05 g. Among the reducing agents, water favoured CO evolution, while the methanol-water system favoured CH4 production. Interestingly, stability studies demonstrated that the LaCoO3 perovskite behaved well and remained stable over numerous cycles without evident deterioration. Furthermore, a suggested photo-induced reaction mechanism was discussed. All of these results demonstrate that LaCoO3 perovskite photocatalysts are capable of efficiently producing solar fuels and can be utilized in solar energy-related applications.